A First Account on Western Mewahang Case Morphology - Gerber, Pascal (Nepalese Linguistics, 2022)
This paper constitutes a first account on the case morphology of Western Mewahang (Kiranti, Trans-Himalayan; Sankhuwasabha district, eastern Nepal), presenting the individual case markers, illustrating their function and morpho-phonological properties and providing historical-comparative notes on the etymologies of selected case markers.